Android-Based Learning Media in Improving Student Motivation and Learning Outcomes : Media Pembelajaran Berbasis Android Dalam Meningkatkan Motivasi dan Hasil Belajar Siswa - Andrian, Dedek Andrian; Nofriyandi, Nofriyandi; Nasution, Arbi Haza; Fadillah, Masrianti; Anggaraini, Dila; Nurhalimah, Siti; Loska, Febri; Septiawan, Akbar (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Learning media is the main support in making learning in the classroom a success. Training through PKM activities can be a place to explore potential and provide space for teachers to hone their skills in making interesting learning videos as learning media. This PKM activity was attended by 42 Meranti Islands Mathematics MGMP teachers in the hall of SMAN 2 Tebing Tinggi Selat Panjang for 2 days, namely Friday-Saturday, 30 to 31 August 2024 using the participant's active participation devotion method. This PKM activity method is carried out in 6 stages, namely: 1) survey and outreach, 2) preparation of plans and preparation of activity materials, 3) counseling, 4) training, 5) implementation of service outcomes, and 6) evaluation. The result of this PKM activity was that teachers' skills in making learning videos with InShot were honed and had a positive impression with 86% of participants succeeding in making interesting learning videos. It can be concluded that this PKM activity was successful and is really needed by teachers to continue to be held by honing other skills which can make teachers more competent in teaching and delivering learning.